Diffusion imaging of mild traumatic brain injury in the impact accelerated rodent model: a pilot study - Kikinis, Zora (Brain Inj, 2017)
PRIMARY OBJECTIVE: There is a need to understand brain pathologic processes following mild traumatic brain injury (mTBI). Previous diffusion MRI studies report axonal injury and edema in the first week after injury in a rodent model. This study aims to investigate the processes occurring one week after injury at time of regeneration and degeneration using dMRI in the impact acceleration rat mTBI model. RESEARCH DESIGN: Eighteen rats were subjected to impact acceleration injury, and three rats served as sham controls. Seven days post-injury, dMRI was acquired from fixed rat brains using a 7T scanner. Group comparison of Fractional Anisotropy (FA) values between traumatized and sham animals was performed using Tract-Based Spatial Statistics (TBSS), a method that we adapted for rats. MAIN OUTCOMES AND RESULTS: TBSS revealed brain white matter regions with increased FA values in the traumatized versus sham rats, localized mainly to the contrecoup region. Regions of increased FA included fiber tracts of the corpus callosum, the anterior commissure, the cerebellar peduncles, the fimbria of the hippocampus, the fornix, the medial forebrain bundle, the optic chiasm, the pyramidal tract, and the spinal trigeminal tract. CONCLUSION: Seven days post-injury, during the period of tissue reparation in the impact acceleration rat model of mTBI, microstructural changes to white matter can be detected using dMRI.